2020
DOI: 10.3390/math8101663
|View full text |Cite
|
Sign up to set email alerts
|

A Note on Geodesic Vector Fields

Abstract: The concircularity property of vector fields implies the geodesicity property, while the converse of this statement is not true. The main objective of this note is to find conditions under which the concircularity and geodesicity properties of vector fields are equivalent. Moreover, it is shown that the geodesicity property of vector fields is also useful in characterizing not only spheres, but also Euclidean spaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
(35 reference statements)
1
4
0
Order By: Relevance
“…It is interesting to observe that the above warped product is short of being a twisted product and thus our Theorem 1 strengthens that the conclusion of Theorem 3.1 in [25] is sharp.…”
Section: Torqued Vector Fields On Spheres and Euclidean Spacessupporting
confidence: 72%
See 1 more Smart Citation
“…It is interesting to observe that the above warped product is short of being a twisted product and thus our Theorem 1 strengthens that the conclusion of Theorem 3.1 in [25] is sharp.…”
Section: Torqued Vector Fields On Spheres and Euclidean Spacessupporting
confidence: 72%
“…Most basic among special vector fields are geodesic vector fields. In [9,25,26] it has been shown that geodesic vector fields are useful in characterizing spheres and Euclidean spaces.…”
Section: Introductionmentioning
confidence: 99%
“…There are other types of vector fields, for instance generalized geodesic vector fields, which are closely related to conformal vector fields (cf. [20]), it will be interesting to investigate the role of generalized geodesic vector fields on compact Ricci almost solitons in making them isometric to the sphere S n (c).…”
Section: Discussionmentioning
confidence: 99%
“…Riemannian manifolds with Killing vector fields has been subject of interest for many mathematicians (cf. [2,[4][5][6][7][8][9][10][11][12][13]). There are other important vector fields, such as Jacobi-type vector fields, geodesic vector fields and torqued vector fields, which play important roles in the geometry of a Riemannian manifold (cf.…”
Section: Introductionmentioning
confidence: 99%
“…There are other important vector fields, such as Jacobi-type vector fields, geodesic vector fields and torqued vector fields, which play important roles in the geometry of a Riemannian manifold (cf. [10,11,[14][15][16]). Moreover, incompressible vector fields have applications in Physics, and as Killing vector fields are incompressible, they have applications in Physics (cf.…”
Section: Introductionmentioning
confidence: 99%